Change in the distribution of house prices across Spanish cities - Catia Nicodemo; Josep M. Raya (Institute for the Study of Labor (IZA), 2012)
This paper presents the quantile estimation of house price between two years, 2004 and 2007 (a boom house price period) in several Spanish cities. We decompose the change in house price distribution into portions: changes in the distributions of the explanatory variables and changes in coefficients over time. Our main results are three. Firstly, from 2004 to 2007, the difference in housing price in Spain is larger at lower and higher percentiles. Secondly, the most important part of the difference in the distribution of housing prices between 2004 and 2007 is explained by coefficients (with all the variables contributing similarly). Thirdly, among cities, we can find a lot of variation in change of house price distribution. With respect to Spain's cities pattern, Madrid, Valencia and Bilbao, are the cities which big difference among them.
urn:nbn:de:101:1-201208096139
Keywords: C1; R21; R31; 330; housing price distribution; housing market; quantile regression; counterfactual distribution; Immobilienpreis; Räumliche Verteilung; Spanien